PENGARUH PRODUKTIVITAS DAN BIAYA MADYA TERHADAP NILAI TAMBAH INDUSTRI FURNITURE DARI KAYU DI INDONESIA - Thian Apriza Pratama Putra (Jurnal Ekonomi Pembangunan, 2014)
The purpose of this study was to find out and how much the productivity and intermediate cost influence the added value of wood furniture industry in Indonesia. This study used the secondary data in the period of 2001-2011. The method used in this study was a qualitative and quantitative descriptive method. Some factors that affect the added-value of wood furniture industry are the level of productivity and the intermediate cost. Productivity is the ratio of the output produced to the labor used in the production process. Intermediate cost is the total cost or raw and auxiliary materials use in the production process. The influence of productivity and intermediate cost variables is indicated by the regression coefficients of each variable. The productivity regression coefficient of 1.818 means that an increase in one unit of productivity would raise the added-value by 1.818. The relationship between the added value and the productivity was positive. The intermediate cost regression coefficient was 0.426, meaning that if the intermediate cost increased by 0.426 then the added value would decrease by 0.426. The relationship between the added-value and the intermediate cost was negative.